Anti-Obesity and Weight Management-Related Antioxidant Potential Properties of Calabrian Pine Extracts: Pinus nigra Subsp. laricio (Poir.) Maire - Mary Fucile; Carmine Lupia; Martina Armentano; Mariangela Marrelli; Ludovica Zicarelli; Claudia-Crina Toma; Giancarlo Statti; Filomena Conforti (Plants)
Natural extracts derived from plants have gained attention as potential therapeutic agents for obesity management. Some natural extracts were demonstrated to inhibit pancreatic lipase and alpha amylase, potentially influencing nutrient absorption and contributing to weight management. Pinus nigra subsp. laricio (Poir.) Maire, commonly known as the Calabrian pine or larch pine, is a subspecies of the black pine native to the mountains of southern Italy and Corsica. This study investigated the phytochemical content and antioxidant (DPPH and β-carotene bleaching assays) and enzymatic (lipase and amylase inhibition) activities of ethanolic extracts from apical shoots and branches, fractionated into n-hexane, dichloromethane, and ethyl acetate. All the extracts were also subjected to a preliminary evaluation of their anti-inflammatory potential by measuring the ability to inhibit nitric oxide (NO) production in RAW 264.7 macrophages. The ethyl acetate branch fraction exhibited the strongest antioxidant activity (DPPH IC50 15.67 ± 0.16 μg/mL), while the total branch extract best inhibited pancreatic lipase (IC50 0.62 mg/mL). Amylase inhibition was strongest in the ethyl acetate apical shoot fraction (IC50 22.05 ± 0.29 µg/mL). The branches’ hexane and dichloromethane fractions showed the greatest anti-inflammatory potential, inhibiting NO production in RAW 264.7 cells with IC50 values comparable to the positive control.